Association of ABO and Rh blood groups to HBV, HCV infections among blood donors in a blood bank of tertiary care teaching hospital in Southern India: A retrospective study - KV, Sreedhar Babu; Bandi, Suresh; Kondareddy, Sindhuja; Madithadu, Anitha (International Journal of Research in Medical Sciences, 2017)
Background: ABO blood group has been found to be associated with the risk of several diseases. Infection with hepatitis B virus (HBV) and hepatitis C virus (HCV) are also the major health problems worldwide. This work was therefore aimed at assessing the ABO and Rh blood group antigens and its association with HBV and HCV seroreactive status among healthy blood donors. Methods: This is a retrospective cross-sectional analytical study carried out in the department of Transfusion Medicine of a tertiary care teaching hospital blood bank for a period of 6 years (January 2009 to December 2014). Data retrieved from blood bank records included the donors’ ABO group, Rh type and the result of HBV, HCV serology. Results: A total number of 41652 blood donors were registered and screened during the study period. The commonest blood group was O constituting 41.5% followed by B-32.6%, A-19.8%, AB-6.1% and Bombay-0.02%. Rh-D positive donors were 92.9% and remaining 7.1% were Rh-D negative. The overall prevalence of HBV and HCV were 2.4% and 0.4% respectively. Among total HBV and HCV seroreactive donors 41.7% and 37.9% were O blood group, B-30.9%, 32.7% A-21.6%, 21.2% and AB-5.7%, 8% respectively. Among the total HBV and HCV seroreactive group, 93.7% and 93.1% had Rh-D positive blood group and remaining 6.3% and 6.9% had Rh-D negative blood group respectively. Conclusion: In this study conducted to determine the predominant blood group antigen and its association with HBV and HCV seroreactivity, there was no association between blood group antigens with these infections.